Sanguisorba officinalis L. Suppresses Triple-Negative Breast Cancer Metastasis by Inhibiting Late-Phase Autophagy via Hif-1α/Caveolin-1 Signaling - Wang, Neng; Muhetaer, Gulizeba; Zhang, Xiaotong; Yang, Bowen; Wang, Caiwei; Zhang, Yu; Wang, Xuan; Zhang, Juping; Wang, Shengqi; Zheng, Yifeng; Zhang, Fengxue; Wang, Zhiyu (Frontiers in Pharmacology, 2020)
Sanguisorba officinalis L. (SA) is a common herb for cancer treatment in the clinic, particularly during the consolidation phase to prevent occurrence or metastasis. Nevertheless, there are limited studies reporting the molecular mechanisms about its anti-metastatic function. It is well demonstrated that autophagy is one of the critical mechanisms accounting for metastasis and anti-cancer pharmacological actions of Chinese herbs. On the threshold, the regulatory effects and molecular mechanisms of SA in suppressing autophagy-related breast cancer metastasis were investigated in this study. In vitro findings demonstrated that SA potently suppressed the proliferation, colony formations well as metastasis process in triple-negative breast cancer. Network and biological analyses predicted that SA mainly targeted caveolin-1 (Cav-1) to induce anti-metastatic effects, and one of the core mechanisms was via regulation of autophagy. Further experiments—including western blotting, transmission electron microscopy, GFP-mRFP-LC3 immunofluorescence, and lysosomal-activity detection—validated SA as a potent late-stage autophagic inhibitor by increasing microtubule-associated light chain 3-II (LC3-II) conversion, decreasing acidic vesicular-organelle formation, and inducing lysosomal dysfunction even under conditions of either starvation or hypoxia. Furthermore, the anti-autophagic and anti-metastatic activity of SA was Cav-1-dependent. Specifically, Cav-1 knockdown significantly facilitated SA-mediated inhibition of autophagy and metastasis. Furthermore, hypoxia inducible factor-1α (Hif-1α) overexpression attenuated the SA-induced inhibitory activities on Cav-1, autophagy, and metastasis, indicating that SA may have inhibited autophagy-related metastasis via Hif-1α/Cav-1 signaling. In both mouse breast cancer xenograft and zebrafish xenotransplantation models, SA inhibited breast cancer growth and inhibited late-phase autophagy in vivo, which was accompanied by suppression of Hif-1α/Cav-1 signaling and the epithelial-mesenchymal transition. Overall, our findings not only indicate that SA acts as a novel late-phase autophagic inhibitor with anti-metastatic activities in triple-negative breast cancer, but also highlight Cav-1 as a regulator in controlling late-phase autophagic activity.